Fault‐tolerant cooperation for time‐varying multi‐vehicle systems with H2/H∞ schemes. Issue 19 (26th July 2019) - Shi, Jiantao; Yang, Yuhao; Sun, Jun; Wang, Ning
Abstract : This study dealt with the fault‐tolerant cooperation problem for a class of time‐varying multi‐vehicle system with actuator faults under the mixed H 2 / H ∞ structure. Through solving coupled backward Riccati equations, a distributed cooperation fault‐tolerant controller was designed for satisfying the proposed H 2 / H ∞ constraints. Finally, a numerical simulation verified the effectiveness of the proposed method.